Entyvio lengthen dose-interval study: lengthening vedolizumab dose interval and the risk of clinical relapse in inflammatory bowel disease. Issue 7 (July 2018) - Chan, Webber; Lynch, Nicole; Bampton, Peter; Chang, Jeff; Chung, Alvin; Florin, Timothy; Hetzel, David J.; Jakobovits, Simon; Moore, Gregory; Pavli, Paul; Radford-Smith, Graham; Thin, Lena; et al.
Abstract : Background: Vedolizumab (VDZ), an α4β7 anti-integrin antibody, is efficacious in the induction and maintenance of remission in ulcerative colitis (UC) and Crohn's disease (CD). In the GEMINI long-term safety study, enrolled patients received 4-weekly VDZ. Upon completion, patients were switched to 8-weekly VDZ in Australia. The clinical success rate of treatment de-escalation for patients in remission on VDZ has not been described previously. Aim: To determine the proportion of patients who relapsed after switching from 4 to 8-weekly VDZ, the mean time to relapse, and the recapture rate when switching back to 8-weekly dosing. Materials and methods: This was a retrospective, observational, multicenter study of patients previously recruited into GEMINI long-term safety in Australia. Data on the demographics and biochemical findings were collected. Results: There were 34 patients [23 men, mean age 49.1 (±13.1) years] and their mean disease duration was 17.6 (±8.5) years. The mean 4-weekly VDZ infusion duration was 286.5 (±48.8) weeks. A total of five (15%) patients relapsed on dose-interval increase (4/17 UC, 1/17 CD) at a median duration from dose interval lengthening to flare of 14 weeks (interquartile range=6–25). Eighty percent (4/5) of patients re-entered remission following dose-interval decrease back to 4-weekly. No clinical predictors of relapse could be determined because of the small cohort size. Conclusion: The risk of patients relapsing when switching from 4 to 8-weekly VDZ ∼15% and is similar between CD and UC. Dose-interval decrease recaptures 80% of patients who relapsed. Therapeutic drug monitoring of VDZ may be of clinical relevance.